0560 Rest-Activity Rhythms are Associated with Prevalent Cardiovascular Disease, Hypertension, Obesity, and Central Adiposity in a Nationally Representative Sample of US Adults. (25th May 2022) - Makarem, Nour; German, Charles; Zhang, Zhanhao; Diaz, Keith; Palta, Priya; Duncan, Dustin; Castro-Diehl, Cecilia; Shechter, Ari
Abstract: Introduction: Prior studies have linked rest-activity rhythms (RAR), a measure of circadian rhythmicity in the free-living setting, to morbidity and mortality. However, evidence is limited on the associations of RAR with adiposity, hypertension, and cardiovascular disease (CVD) in a nationally representative sample of US adults. Methods: Participants were 4, 822 adults (age:≥20y) from the 2013-2014 National Health and Nutrition Examination Survey, who participated in the physical activity monitoring examination. Data from a wrist-worn ActiGraph GT3X+ accelerometer were used to estimate non-parametric 24-h RAR variables. Logistic models adjusted for age, sex, race/ethnicity, education, marital status, smoking, and alcohol use were used to evaluate associations of RARs with prevalent CVD (self-reported), hypertension (blood pressure≥130/80mmHg or medication use), obesity (BMI≥30kg/m2), and central adiposity (waist circumference>102cm for men and >88cm for women). Results: Participants (mean age: 48y, 53% female, 33% racial/ethnic minority) in the highest vs. lowest tertile of relative amplitude, indicative of more robust RAR, had lower odds of prevalent CVD (OR(95%CI):0.47(0.25-0.87)), hypertension (OR(95%CI):0.63(0.40-0.99)), obesity (OR(95%CI):0.50(0.36-0.69)), and central adiposity (OR(95%CI):0.50(0.36-0.69)). Those in the highest vs. lowest tertile of M10 counts, indicating a more active wake period, had 66%, 54%, and 39% lower odds of CVD, obesity, and central adiposity, respectively. In contrast, participants in the highest vs. lowest tertile of intradaily variability, indicative of more fragmented RARs, had >2-fold (OR(95%CI):2.40(1.23-4.70)) and 40% (OR(95%CI):1.40(95%CI:1.04-1.88)) higher CVD and obesity odds, respectively. Further, those in the highest vs. lowest tertile of L5 midpoint, indicative of a later sleep period, had 68% and 41% higher odds for CVD and hypertension, while those with higher L5 counts, indicative of less efficient sleep, had 72%, 57%, and 79% higher hypertension, obesity, and central adiposity odds, respectively. A statistically significant linear trend was observed across RAR tertiles for all associations (p-trend<0.05). Conclusion: Robust RAR, an active wake period, and an earlier and more efficient sleep period are associated with lower odds for CVD, hypertension, obesity, and central adiposity, with evidence of a dose-response relationship. The timing, regularity, and periodicity of sleep-wake and rest-activity patterns may represent an important target for reducing cardiovascular risk in adults. Support (If Any): NHLBI R00-HL148511; AHA grant #855050